A Status Data Transmitting System for Vessel Monitoring - The Anh Nguyen Dinh; Huy Le Xuan; Tuan Anh Vu; Duong Bach Gia (Institute of Advanced Engineering and Science, 2018)
This paper presents a status data transmitting system suitable for vessel monitoring. The system consists of four main parts, which are a status data module, a frequency synthesizer, a power amplifier and a horn antenna. The status data module packs information of the identification, longitude, latitude and state of the vessel into data frames. FSK/MSK/GMSK schemes were used to modulate the data. The frequency synthesizer was designed with very high stability over temperature and very low frequency tolerance. The power amplifier provides 130 W output power at S band. The impedance bandwidth of the horn antenna can be controlled using the beveling technique.